Developmental control of spike-timing-dependent plasticity by tonic GABAergic signaling in striatum - Valtcheva, Silvana; Paillé, Vincent; Dembitskaya, Yulia; Perez, Sylvie; Gangarossa, Giuseppe; Fino, Elodie; Venance, Laurent (Neuropharmacology, 2017)
Activity-dependent long-term potentiation (LTP) and depression (LTD) of synaptic strength underlie multiple forms of learning and memory. Spike-timing-dependent plasticity (STDP) has been described as a Hebbian synaptic learning rule that could account for experience-dependent changes in neural networks, but little is known about whether and how STDP evolves during development. We previously showed that GABAergic signaling governs STDP polarity and thus operates as a Hebbian/anti-Hebbian switch in the striatum. Although GABAergic networks are subject to important developmental maturation, it remains unclear whether STDP is developmentally shaped by GABAergic signaling. Here, we investigated whether STDP rules are developmentally regulated at corticostriatal synapses in the dorsolateral striatum. We found that striatal STDP displays unidirectional plasticity (Hebbian tLTD) in young rats (P7-10) whereas STDP is bidirectional and anti-Hebbian in juvenile (P20-25) and adult (P60-90) rats. We also provide evidence that the appearance of tonic (extrasynaptic) GABAergic signaling from the juvenile stage is a crucial factor in shaping STDP rules during development, establishing bidirectional anti-Hebbian STDP in the adult striatum. Thus, developmental maturation of GABAergic signaling tightly drives the polarity of striatal plasticity. [Display omitted] •Striatal STDP is developmentally regulated.•Blockade of GABAAR signaling promotes Hebbian STDP, regardless of the developmental stage.•Tonic GABAergic signaling is crucial in shaping STDP during development.